1992
DOI: 10.1254/jjp.58.407
|View full text |Cite
|
Sign up to set email alerts
|

Different Pathways for Ca2+ Influx and Intracellular Release of Ca2+ Mediated by Muscarinic Receptors in Ileal Longitudinal Smooth Muscle.

Abstract: Muscarinic receptor-mediated elevations in intracellular Ca 2-1 concen tration ([Ca 21]i) in the longitudinal smooth muscle of guinea pig ileum were studied by the use of fura-2 fluorescence. Dose-response analysis indicated a difference in the potencies of carbachol (CCh) to increase [Ca 2 +]; in the presence and absence of ex tracellular Ca 2+. For the increase in [Ca 2+]; due to Ca 2+ release from intracellular stores in the absence of extracellular Ca 2+' the ED50 value of CCh was 3 X 105 M. On the other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In the present study, pilocarpine and McN‐A343 failed to evoke I K‐Ca , but were able to inhibit the I K‐Ca ‐evoking activity of carbachol, indicating their antagonist behaviour at M 3 receptors. Such properties are also indicated from other studies in which their effects on phosphoinositide turnover and Ca 2+ store‐dependent changes in [Ca 2+ ] i or tension were examined (Gardner & Mitchelson, 1988; Hishinuma et al ., 1997; Morel et al ., 1997; Wang et al ., 1992). Both agonists also shifted the carbachol concentration‐effect curve for I cat activation to the right with depression of the maximum response (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, pilocarpine and McN‐A343 failed to evoke I K‐Ca , but were able to inhibit the I K‐Ca ‐evoking activity of carbachol, indicating their antagonist behaviour at M 3 receptors. Such properties are also indicated from other studies in which their effects on phosphoinositide turnover and Ca 2+ store‐dependent changes in [Ca 2+ ] i or tension were examined (Gardner & Mitchelson, 1988; Hishinuma et al ., 1997; Morel et al ., 1997; Wang et al ., 1992). Both agonists also shifted the carbachol concentration‐effect curve for I cat activation to the right with depression of the maximum response (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…CCh was suggested to elicit Ca 2+ release from SR only at a higher concentration than that necessary for an increase in the Ca 2+ influx in the guinea pig taenia coli (22). It was also suggested that Ca 2+ release from SR was activated by high concentrations of CCh but not by other muscarinic agonists, pilocarpine and oxotremorine that increase Ca 2+ influx from outside of the cells in longitudinal muscle of the guinea pig ileum (23). Although all these results indicate the importance of Ca 2+ influx in smooth muscle contraction, the results on the proximal colon in the present study is conspicuous among them.…”
Section: Discussionmentioning
confidence: 99%
“…The rise in cytoplasmic Ca 2+ concentration via activation of muscarinic M 3 receptors could be via a Ca 2+ release pathway from intracellular stores and/or a Ca 2+ influx pathway from the extracellular space (Brading & Sneddon, 1980; Parekh & Brading, 1992; Wang et al , 1992). In the absence of extracellular Ca 2+ , and in contrast to the effect of carbachol, neither McN‐A‐343 nor AHR‐602 induced a contractile response.…”
Section: Discussionmentioning
confidence: 99%